Islam in a globalized world : negotiating faultlines - Hasan, Mushirul (Gurgaon : ImprintOne, 2010)
Contributed articles.
Includes bibliographical references and index.
Keywords: Islam -- 21st century; Islam -- India; Islam and world politics